RESPONSES OF ACCOUNTABILITY TRANFORMATION PRACTICED IN MULTIPLE LEVEL OF INSTITUTIONAL LOGICS FOR BEING AUTONOMOUS STATE UNIVERSITIES IN INDONESIA - Utomo, Dwi Cahyo (JURNAL AKUNTANSI DAN AUDITING, 2019)
This study investigates accountability practices of Indonesian state universities during the reform implementation for being autonomous universites called as PTN Badan Hukum. Although the reform has been implemented based on government regulation, lack of empirical study can be viewed in published articles. For that reason, this study is addresed to filling the lack of accountability research in the reform of state universities in Indonesia. The context of the reform is the adoption of autonomous universities that are more close to the concept of privatisation affected by the internationalization objective of national agenda. Interpretive research approach is adopted to develop inductively a conceptual perspective based on central phenomenon. Moreover, the cases of the study are three Indonesian state universitiesÂ  which implement the form of autonomous state university with pseudo named as UG, UD and UA. Straussian grounded theory approach was adopted in data analysis and collection. The central phenomenon of substantive grounded theory is labelled as multiple accountability responses in various institutional logic during transformation process of state universities that have been transformed from fully governed by Indonesia government become autonomous entities. The main finding of the study explains the presence of various institutional accountibility logics practiced in the context of internationalization process of Indonesia higher education institutions. The various institutional logics arise from personal, professional, managerial and public accountability logics. The various accountability logics display from two different environmental background that are university with less and high internationalization. Less and moderate conflict are resulted from low and high internationalization achievement respectively. The practice of accountability seem displaying more emphasize on public accountability logic in social level, managerial accountability logic in organizational level, personal and professional in individual level. The contribution of this research relates to empirical findings that enrich higher education accountability research in developing countries, employs interpretive methodology and grounded theory, and provides incremental development of institutional logics theory in explaining organizational change in a specific context.